No influence of face familiarity on the cheerleader effect - Kramer, Robin S. S.; Javorková, Natália; Jones, Alex L. (Visual cognition, 2024)
The cheerleader effect describes how faces are perceived as more attractive when presented in a group rather than alone. Given differences in how familiar versus unfamiliar faces are perceived and represented, we hypothesized that the cheerleader effect may be diminished/absent for familiar faces. In Experiment 1, targets were rated for attractiveness when presented alone and in groups, with these selected to span the continuum of prior familiarity. Our results identified the cheerleader effect, alongside an increase in attractiveness with increasing familiarity, but no interaction between these two effects. In Experiment 2, we instructed participants to rate the target "person" rather than "face" to increase the salience of any pre-existing impressions. Again, the results showed no influence of familiarity on the size of the cheerleader effect. Taken together, the cheerleader effect was robust with respect to face familiarity, perhaps suggesting underlying mechanisms that are more general rather than face specific.